2012
DOI: 10.1007/s11033-012-2255-y
|View full text |Cite
|
Sign up to set email alerts
|

Antisense-overexpression of the MsCOMT gene induces changes in lignin and total phenol contents in transgenic tobacco plants

Abstract: Initially, we isolated the caffeic acid O-methyltransferase (COMT) gene from Miscanthus sinensis (accession number HM062766.1). Next, we produced transgenic tobacco plants with down-regulated COMT gene expression to study its control of total phenol and lignin content and to perform morphological analysis. These transgenic plants were found to have reduced PAL and ascorbate peroxidases expression, which are related to the phenylpropanoid pathway and antioxidant activity. The MsCOMT-down-regulated plants had de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…These results demonstrated that the efficiency of using an antisense approach with a heterologous gene, as shown previously using an endogenous homologous gene (Tottey et al 2003). The antisense expression of a heterologous gene results in reduced expression level of the endogenous homologous gene, which has been confirmed by the expression of antisense FBP1 (from Phaseolus vulgaris) in Arabidopsis (Bindschedler et al 2006), and antisense MsCOMT (from Miscanthus sinensis) and antisense GMPase (from tomato) in tobacco plants Seong et al 2013). Feedback inhibition of chlorophyll synthesis is observed.…”
Section: Discussionsupporting
confidence: 80%
“…These results demonstrated that the efficiency of using an antisense approach with a heterologous gene, as shown previously using an endogenous homologous gene (Tottey et al 2003). The antisense expression of a heterologous gene results in reduced expression level of the endogenous homologous gene, which has been confirmed by the expression of antisense FBP1 (from Phaseolus vulgaris) in Arabidopsis (Bindschedler et al 2006), and antisense MsCOMT (from Miscanthus sinensis) and antisense GMPase (from tomato) in tobacco plants Seong et al 2013). Feedback inhibition of chlorophyll synthesis is observed.…”
Section: Discussionsupporting
confidence: 80%
“…The silencing of HCT gene resulted in the decrease in lignin content and the change in lignin composition in the callus of Pinus radiata [55]. Antisense overexpression of the MsCOMT gene induces changes in lignin and total phenol contents in transgenic tobacco plants [56]. The transcription of lignin synthesis genes 4CL and CAD are upregulated, leading to lignin deposition, thickening of secondary cell walls, and enhancing of the salt-resistance and permeability of birch and apple [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…The transgenic tobacco plants with down-regulated COMT gene expression demonstrate that COMT plays a crucial role related to controlling lignin and phenol content in plants. Moreover, COMT activity may be related to flavonoid production in the plant lignin pathway [ 47 ]. For this, studies have shown that plants strengthen their cell walls through the accumulation of phenolic compounds, which was thought to be a ubiquitous defense response [ 48 ].…”
Section: Discussionmentioning
confidence: 99%